Clinical experience in the treatment and prognosis of seven cases of Cronkhite-Canada syndrome - Jisu Bae; Minjee Kim; Eun Ran Kim; Young-Ho Kim; Dong Kyung Chang; Ji Eun Kim; Sung Noh Hong (Medicine, 2026)
Cronkhite-Canada syndrome (CCS) is a rare, nonhereditary gastrointestinal polyposis syndrome. The rarity of CCS has led to a limited understanding of its optimal management and prognosis. We aimed to share our experience with 7 CCS patients, investigating the clinical characteristics, diagnostic approaches, treatment strategies, and prognoses we have established. We conducted a retrospective analysis of adult patients diagnosed with CCS between January 2016 and December 2024. The primary outcome was to evaluate the diagnostic findings and treatment course. Secondary outcomes included the assessment of complications and prognoses during the follow-up period. A weighted scoring system was developed to evaluate treatment response. Among the 11 initially identified patients, 7 patients were included. All patients presented with alopecia, and the majority exhibited skin pigmentation (85.7%) and nail dystrophy (57.1%). Gastric and colonic polyposis were confirmed in all cases. Treatment strategies included corticosteroids, azathioprine, mesalazine, and methotrexate (MTX). Complete remission (CR) of gastric and colonic polyps was achieved in 1 patient (14.3%) after 16.2 months of treatment. One patient (14.3%) was diagnosed with a malignant neoplasm of the brain during follow-up. No mortalities were reported during the study period. Our findings suggest that while corticosteroids remain the primary treatment, individualized approaches incorporating immunomodulators may improve outcomes. Long-term surveillance is crucial due to the potential for malignant transformation. Further research is needed to optimize management strategies and understand the genetic basis of CCS.